Detection of focal lesions in the clot section with negative bone marrow aspirate and trephine biopsy—A series of 5 cases - Vandana Bhatti; Naveen Kakkar (Indian Journal of Pathology and Microbiology)
Bone marrow aspiration and trephine biopsies are commonly used procedures in clinical practice. The practice of making a clot section by using the leftover blood from the bone marrow aspirate material is not a commonly followed practice across centers. A clot section has the advantage of studying the added material with an increased possibility of detecting focal lesions such as myeloma, lymphoma, granuloma, and metastasis in the bone marrow. Bone marrow aspirate, trephine biopsy, and clot section were compared for the detection of focal lesions in a series of 5 patients, 3 of who presented with a history of fever and 2 were already diagnosed cases of Hodgkin lymphoma. Focal lesions were detected in the 5 cases in the clot section alone, whereas bone marrow aspirate and trephine biopsy did not show any focal lesion. Granulomatous infiltration was detected in 3 patients, and lymphomatous infiltration was detected in 2 patients in the clot section, whereas bone marrow aspirate and trephine biopsy were negative for any focal lesion in all 5 cases. A clot section is particularly useful in the detection of bone marrow lesions with a focal distribution. Hence, it must be studied alongside bone marrow aspirate smears, touch smears, and trephine biopsy to increase the diagnostic yield.